A comparative study and unification of two methods for controlling dynamically substructured systems. (24th August 2016) - Stoten, David Paul
Summary: This paper addresses the problem of advanced testing of systems via the principle of dynamic substructuring. Use is made of the hybrid simulation (HS) scheme framework to develop a new method of synthesis for the dynamically substructured system (DSS) scheme of Stoten and Hyde. Principal reasons for doing this are (i) to improve upon the original method of DSS synthesis by adopting the more intuitive framework of HS and (ii) to enable the amalgamation of HS and DSS into a unified substructured system (USS) scheme, so that the significant advantages of DSS can be incorporated into an existing HS scheme as a straightforward retrofit. Having established the common framework for HS/DSS, the paper also illustrates, by way of an example, compensator/controller synthesis for the two schemes, together with their advantages and disadvantages. In doing this, both schemes are retained in their basic forms, that is, there are no additional control embellishments used in this work, such as delay compensation, adaptive control, or other advanced control methods. In order to maintain as much transparency as possible, use is made of well‐known classical control techniques. Common problems associated with the substructure testing technique are also investigated, including the effects of physical parameter uncertainty, pure delays in signals, and a 'split‐mass' in the substructure formulation. It is shown that, although the new formulation of controlled DSS requires more design effort than compensated‐HS, the advantages of DSS in terms of stability and robustness significantly outweigh this small disadvantage at the design stage. Copyright © 2016 John Wiley & Sons, Ltd.